Análise do efeito mutagênico e recombinogênico de diferentes fármacos anti-hipertensivos em células somáticas de Drosophila melanogaster - Oliveira, Rosiane Gomes Silva (2015)
Disturbances in the formation of angiotensin II (Ang II) can cause hypertension, cardiovascular, kidney problems and even cancer. Drugs such as inhibitors of angiotensin converting enzyme (ACE) inhibitors and angiotensin receptor blockers (ARB) have properties in regular the formation of Ang II and, possibly, effects antiproliferative and antioxidant. This study aimed to evaluate the mutagenic effects / recombinogenic of two ACE inhibitors (captopril and perindopril) and of an angiotensin receptor blockers (losartan potassium), by testing for mutation detection and somatic recombination in wings Drosophila melanogaster, as well as possible modulating effects of these drugs against the damage induced by doxorubicin (DXR), an antitumor drug whose mechanism of action involves intercalation of DNA and formation of free radicals. For the treatment, the larvae trans-heterozygous descendants of crossing high bioactivation (HB) and standard crossing (ST) were subjected to chronic treatment 48h. In this procedure were used five concentrations of each drug, individually or associdas DXR (0.125 mg/mL). The results showed that captopril has no mutagenic effect or recombinogêncio on both junctions and also proved unable to modulate the effects induced by DXR. Perindopril showed no mutagenic or recombinogenic effect on ST descendants, however, these effects was expressed in HB descendants. Losartan potassium did not show mutagenic effects or recombinogenic in both crosses (ST and HB), however, in the co-treatment with DXR showed modulating effect, able to reduce the damages induced by chemotherapy. In conclusion, the results suggest that the antioxidant effects of captopril were not observed in this experiment, because captopril was not able to reduce the damage induced by DXR; while perindopril to be biometabolizado by cytochrome P450 enzymes showed potential to induce recombinogenic events; and the modulating effect presented by losartan potassium seems is related to its ability to alter the permeability of the membrane and activate antiproliferative mechanisms.